Value-Based Educational Leadership: A Literature Review On Sports Education - Lengkong, Indira Krisanti; Ahmad, Masduki; Suryadi, Suryadi (Journal Coaching Education Sports, 2025)
This paper discusses the concept of value-based educational leadership as a strategic approach to improving the quality of education through the integration of moral and ethical values ​​in the management and operation of educational institutions. This approach is relevant in facing global challenges, such as social crises, technological change, and cultural dynamics, which require leaders with integrity, transparency, and social responsibility. Based on the literature review, value-based leadership not only contributes to the achievement of academic goals but also the formation of student character. This study analyzes the role of value-based leadership in creating a positive organizational culture, motivating teachers, and building a holistic learning environment. In addition, this paper identifies the main challenges in implementing these values, such as the challenge of resistance to change that can be overcome with the active involvement of stakeholders, resource constraints, and the influence of external factors. The results of the study indicate that with a clear vision, community participation, and the use of information technology, value-based leadership can be the key to creating inclusive and sustainable educational institutions. The practical implications of this approach are the development of educational policies that focus more on strengthening character and collaboration between stakeholders.